Employment of a Silica Gel Formulated from Steel Slag to Remove Lead, Nickel and Cadmium in Aqueous Solution - Chouchane, Toufik; Boukari, Atmane; Chouchane, Sabiha; Khireddine, Ouahida; Abedghars, Mohamed T.; Meradi, Hazem (Iraqi Journal of Science, 2025)
In this study, silica gel (SG) derived from steel slag (SS) was utilized as an adsorbent for the removal process of lead, nickel and cadmium, both individually and in combination. Experimental results demonstrated that steel slag was successfully converted into silica gel by chemical and thermal treatments, yielding a material composed of 95.61% silica with a specific surface area of 472.38 m2/g. Monitoring of adsorption processes highlighted the considerable impact of contact time, pH, temperature, stirring speed, and initial concentration on these processes. The amounts absorbed after 50 minutes of contact for lead, nickel, and cadmium were 144.74, 133.14 and 126.89 mg/g. However, for the mixture, it had reached 119.12 mg/g after 70 minutes of agitation. Adsorption isotherms demonstrated that the adsorption of the ions examined occurs on a homogeneous monolayer surface. The separation factor (RL) and intensity of sorption (1/n) showed that the processes performed were favorable. Kinetic analysis revealed that the adsorption processes followed pseudo-second-order kinetics, depending on both external and internal diffusion. Thermodynamically, the processes were found to be exothermic, spontaneous, and less entropic. The values change in free energy, enthalpy variation, and Temkin constant (bT) have shown that these processes were characterized by adsorption of a physical nature.